Let`s hear it from the kids! Examining the experiences, views, and needs of highly committed children involved in youth sport - Harris, J. J.; Collins, D.; Nash, C. (The Sport Psychologist, 2023)
Sport specialization and intensive training programs are becoming increasingly popular, but there is an ongoing debate as to their value. This study explored how children experience arduous, specialized training and whether they find it enjoyable and meaningful. We also examined their perspective of what parental involvement they needed. One hundred three participants filled out an online questionnaire. Results demonstrated that the participants were almost without exception highly committed to their training. They acknowledged the documented downsides, such as long hours, pain, and repetition, but expressed resounding commitment, giving little indication that they looked for change. They admitted that they preferred their parents not to be involved with their coaching and disclosed that showing pride for them was their main wish. This study demonstrates that passion can engender powerful commitment and satisfaction from training that may be sometimes considered by others as too challenging for a young person to undertake.